Productivity and Land Use Efficiency of Maize Varieties under Different Row Spacings in a Maize–Finger Millet Relay Cropping System of the Mid-Hills of Nepal - Chaulagain, Bhimsen; Bhattarai, Rajendra Kumar; Timalsina, Himal Prasad; Neupane, Reshama; Kaduwal, Sangita (Agronomy Journal of Nepal, 2025)
Relay cropping of maize with finger millet (maize/finger millet) is the predominant cropping system for sustaining food security situation in the hilly regions of Nepal. Two-year field experiments (2023–2024) were conducted at research field of National Agronomy Research Centre, Khumaltar, Lalitpur, Nepal to evaluate the effects of maize varieties and maize row spacing on growth, yield, and land use efficiency in a maize–finger millet relay cropping system. The study used a split-plot design with three replications. Three maize row spacings (75, 100, and 150 cm) were used as main plots and four maize varieties (BGBYPOP, Arun-2, Manakamana-4, BISCO 940 NEW) as subplots. Finger millet seedlings were transplanted under standing maize 28–35 days after sowing. Data on growth, yield, and land equivalent ratio (LER) were recorded and analyzed over two seasons. Results showed that maize variety significantly (P<0.05) influenced system productivity, whereas row spacing had limited effect on LER. BGBYPOP produced the highest LER (1.65), followed by BISCO 940 NEW (1.62), indicating superior land use efficiency, while narrow row spacing (75 cm) produced 7.42tha-1 maize yield. Maize varieties Arun-2 and Manakamana-4 gave higher finger millet grain yield (4.19–4.23 t ha⁻¹) by reducing inter-crop competition. Maize-finger millet relay cropping with promising maize varieties should be done continuously to recommend maize variety for relay cropping system.